The Effect of Newtonian Dynamics STEM-Integrated Learning Strategy to Increase Scientific Literacy of Senior High School Students - Listiana, Listiana; Abdurrahman, Abdurrahman; Suyatna, Agus; Nuangchalerm, Prasart (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2019)
This research aimed to examine Sains, Technology, Engineering, Mathematics (STEM) learning approach effectivity in increasing scientific literacy of senior high school students. The research involved 67Senior High School 5 students Bandar Lampung in Lampung Province, Indonesia. The research design used was the-Equivalent Control Group Pretest and Posttest Design. The experimental class used STEM Learning Approach, and the control class used a scientific approach. The data was collected using pretest and posttest score of scientific literacy inventory. The Effectiveness analysis was done using the Normalized Gain (N–Gain) and Effect Size. Based on the research, the average score of the scientific literacy skill with N-gain of experimental classes was 0.55 and control class was 0.49, both classes were in medium category achievement. The result of effect size test showed that STEM learning approach has an effect size in the medium category of 0.24. Furthermore, based on an analysis of T-test results, there was a difference between the N-gain average score of the students' scientific literacy skill between experimental class and control class. The students who learned with STEM learning approach has a significantly higher degree of scientific literacy skill than those who learned with the scientific approach. So the conclusion in this research is that the students taught using the STEM approach are in the "conceptual" category which is better in explaining the concept, able to describe the relationship between these concepts, and able to analyze alternative solutions and procedural skills and understanding of the process of discovering science and technology.